Molecularly imprinted polymer waveguides for direct optical detection of low-molecular-weight analytes - Sharma, Nityanand (2014)
New composite layer architecture of 3D hydrogel polymer network that is loaded with molecularly imprinted polymer nanoparticles (nanoMIP) is reported for direct optical detection of low-molecular-weight compounds. This composite layer is attached to the metallic surface of a surface plasmon resonance (SPR) sensor in order to simultaneously serve as an optical waveguide and large capacity binding-matrix for imprinted target analyte. Optical waveguide spectroscopy (OWS) is used as a label-free readout method allowing direct measurement of refractive index changes that are associated with molecular binding events inside the matrix. This approach is implemented by using a photo-crosslinkable poly(N-isopropylacrylamide)-based hydrogel and poly[(ethylene glycol dimethylacrylate)-(methacrylic acid)] nanoparticles that are imprinted with l-Boc-phenylalanine-anilide (l-BFA, molecular weight 353 g mol−1). Titration experiments with the specific target and other structurally similar reference compounds show good specificity and limit of detection for target l-BFA as low as 2 × 10−6 m.